Breakdown Characteristic Research on Propylene Carbonate After Nano-Modification - Zicheng, Zhang; Diangeng, Li; Yanpan, Hou (Frontiers in Physics, 2022)
Propylene carbonate (PC) has the advantages of great permittivity, high breakdown strength, and great environmental adaptability. However, the applications of propylene carbonate in pulsed power systems have been restricted by the significant polarity effect (differences between the positive breakdown strength and the negative breakdown strength). In this article, the breakdown characteristics of PC by nano-modification under microsecond pulse have been systematically studied. The results showed that the positive breakdown strength is about twice that of the negative breakdown strength of pure PC. After nano-modification, the negative breakdown strength increases significantly, while the positive breakdown strength decreases. The energy band theory of nanofluids was established.